Hubungan Pembelian Makanan Online dan Kebiasaan Makan Dengan Status Gizi Mahasiswa Indekos di Kota Bandar Lampung - Nurjannah, Afiifah Suci; Dalimunthe, Nathasa Khalida; Kustiani, Ai (CV. Rayyan Dwi Bharata, 2024)
Nutritional status describes an individual's health condition based on their Body Mass Index (BMI), which is categorized into levels such as severely underweight, mildly underweight, normal, mildly overweight, and severely overweight. Factors influencing nutritional status include eating habits and social media exposure. Eating habits refer to the regular practices or patterns adopted by an individual to fulfill physiological, social, and emotional needs through the consumption of necessary food for adequate nutritional intake. Meanwhile, prolonged exposure to social media can lead to an individual frequently encountering recommended posts, including food-related content, thereby increasing the desire to try those foods. Currently, in Indonesia, some platforms that provide online food delivery services are GoFood, GrabFood, and Shopee Food. The general aim of this study is to determine the relationship between online food purchasing and eating habits with the nutritional status of college students living in boarding houses in Bandar Lampung city. The research method used in this study is quantitative, employing a cross-sectional approach. Data collection was conducted using a microtoise to measure height, a stepping scale to measure weight, a modified SQ-FFQ form to assess eating habits, and a questionnaire to evaluate online food purchasing behavior. The chi-square test results indicate a p-value of 0.187, demonstrating no significant relationship between eating habits and the nutritional status of college students living in boarding houses in Bandar Lampung. In contrast, the chi-square test results indicate a p-value of 0.004, showing a significant relationship between online food purchasing and the nutritional status of these students. College students are advised to be more cautious when choosing foods, considering health factors and avoiding the influence of images or videos of food that might affect eating behaviors.